If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -1(-4y) = 8 Remove parenthesis around (-4y) 18 + -1 * -4y = 8 Multiply -1 * -4 18 + 4y = 8 Solving 18 + 4y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 4y = 8 + -18 Combine like terms: 18 + -18 = 0 0 + 4y = 8 + -18 4y = 8 + -18 Combine like terms: 8 + -18 = -10 4y = -10 Divide each side by '4'. y = -2.5 Simplifying y = -2.5
| 12a-16=8a+4 | | 5k-1=24 | | y+7(-2)=11 | | B=nx+x | | 5x+17=2x+5 | | 8.00(4.00+x)=3 | | y+7(0)=11 | | 14x^4y^7/6x^5y^4 | | 3x+12=24-2x | | 5=-3+m/8 | | 2b+6=10 | | y+7(4)=11 | | 4x+-5=2(2x+1) | | 8x+10x=44 | | 4(b-1)+2(3+b)=9 | | 0=8y-56 | | 5x+51=x+19 | | 5+9z=10+9z | | x+100+45=180 | | 144t^2+1/t^2+24 | | 2x-(56)=5 | | 144t^2+1/t^2 | | -12x-3=27-9x | | (12-15n)/(5n^2+6n-8) | | k/3=-17 | | c-68=-121 | | ((x+7)/(x+3))=((x-2)/(x+1))+1 | | 6x-3=3-6x | | x/7-2=9/14 | | x-3=21.6 | | 4*2+1= | | 2x+16=y |